Publishing Rights As A Solution To The Economic Crisis Of Mainstream Television Media? A Critical Analysis Of The Indonesian Press Council’S Proposal In Facing The Hegemony Of Digital Platforms - Henry Sianipar; Udi Rusadi; Titi Widaningsih (Asosiasi Dosen Muda Indonesia, 2025)
The dominance of global digital platforms such as Google, Meta, and TikTok has triggered an economic crisis within Indonesia’s mainstream television industry, as evidenced by a significant decline in advertising revenue and increased audience fragmentation. This study critically examines the Indonesian Press Council’s proposal on Publishing Rights as a response to the economic imbalance between traditional media and digital platforms. By employing theoretical frameworks from Political Economy of Communication, Platform Capitalism, and Media Regulation, the research evaluates the mechanisms and implementation potential of Publishing Rights in the Indonesian context and draws comparisons with international practices in Australia, France, Canada, and South Korea. A qualitative approach is applied through policy analysis and comparative studies, supported by data obtained from policy documents, industry reports, and in-depth interviews. The findings indicate that Publishing Rights hold promise as an effective policy instrument to rebalance the digital media ecosystem, strengthen the resilience of quality journalism, and enhance the bargaining power of national media against global tech giants. Nevertheless, substantial implementation challenges remain, particularly resistance from digital conglomerates and the need for regulatory harmonization. The study recommends strengthening the legal framework through dedicated legislation, establishing a Digital Media Resilience Authority, and adopting a revenue-sharing model based on content production contribution. In conclusion, Publishing Rights have the potential to serve as a strategic pillar for the economic recovery of the television media industry, provided they are supported by an inclusive policy design and rigorous oversight.